The Role of Violated Caregiver Preferences in Psychological Well-Being When Older Mothers Need Assistance - Suitor, J. Jill (Oxford University Press, 2013)
Purpose: Theory and research suggest that congruence between individuals’ preferences for future care and the patterns of care received will affect well-being. In this article, we explore whether older mothers’ psychological well-being was affected by the children they preferred as future caregivers and provide assistance at a later point when the mothers experience illness or injury. Design and Methods: In this article, we use a combination of quantitative and qualitative data collected from 234 older mothers at two points 7 years apart, beginning when the mothers were 65–75 years of age. Results: Multivariate analyses demonstrated that mothers who received assistance from children whom the mothers did not identify as their preferred future caregivers reported higher depressive symptoms at the second wave; receiving care from children identified as preferred caregivers did not affect well-being. Qualitative data suggested that these patterns occurred because the “alternate” caregivers did not possess the socioemotional attributes of preferred children. Implications: These findings contribute to a growing body of research demonstrating the consequences of violated preferences, particularly when individuals are in need of support in later life.